2009
DOI: 10.3109/01913120903275642
|View full text |Cite
|
Sign up to set email alerts
|

SEM Study of Apical Morphological Alterations in Primary Teeth with Vital and Necrotic Pulps

Abstract: This study evaluated, by SEM, the morphology of human primary teeth roots. Twenty-four teeth were divided into 3 groups: pulp vitality (group I) and pulp necrosis without (group II) and with apical periodontitis (group III). Roots were analyzed by the presence of periodontal ligament (PDL) fibers and resorption areas. In groups I and II, presence of PDL fibers and absence of resorption were observed in all cases (100%), while all specimens (100%) of group III showed no PDL fibers and resorption areas. In concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(23 reference statements)
0
4
0
1
Order By: Relevance
“…35 Technical issues related to the access of endodontic files to the bacteria present in the root canal, however, might prevent effective cleaning of the root canal, and therefore bacteria can remain in the system, especially in the external areas of resorption of cementum. 36,37 Therefore, root canal dressing has been used as a clinical step to enhance the disinfection of the root canal, dentin tubules, and apical cementum resorption areas. 2,35,38 It has been demonstrated that 14 days of root canal dressing is enough for hydroxyl ions from calcium hydroxide to penetrate the root canal dentin and reach out the cementum surface, increasing the pH of this area.…”
Section: Discussionmentioning
confidence: 99%
“…35 Technical issues related to the access of endodontic files to the bacteria present in the root canal, however, might prevent effective cleaning of the root canal, and therefore bacteria can remain in the system, especially in the external areas of resorption of cementum. 36,37 Therefore, root canal dressing has been used as a clinical step to enhance the disinfection of the root canal, dentin tubules, and apical cementum resorption areas. 2,35,38 It has been demonstrated that 14 days of root canal dressing is enough for hydroxyl ions from calcium hydroxide to penetrate the root canal dentin and reach out the cementum surface, increasing the pH of this area.…”
Section: Discussionmentioning
confidence: 99%
“…The potential explanation for this phenomenon could be attributed to the proximity of the permanent tooth germ to the bifurcation and apices of the primary teeth. This closeness, coupled with the existence of numerous root and accessory canals, increases the likelihood of primary tooth infection infiltrating the apical and furcation regions, thereby impinging upon the successive permanent tooth follicle [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential explanation for this phenomenon could be attributed to the proximity of the permanent tooth germ to the bifurcation and apices of the primary teeth. This closeness, coupled with the existence of numerous root and accessory canals, increases the likelihood of primary tooth infection infiltrating the apical and furcation regions, thereby impinging upon the successive permanent tooth follicle [5]. According to some authors, degradation of the overlying osseous tissue due to periapical infection of the deciduous dentition expedites the emergence of succeeding permanent teeth [6]; however, other studies posit that it retards the eruption of permanent teeth [7].…”
Section: Introductionmentioning
confidence: 99%
“…The thin pulpal floor, higher prevalence of accessory canals, and wider dentin tubules found in primary teeth result with high permeability of pulpal floor and [3–7]; these factors are generally considered to cause furcation lesions in primary teeth with irreversible pulpitis or necrotic pulps. Moreover, the permeability of the pulpal floor may increase following lesion formation, since Da Silva et al [8] reported that there were resorption areas on the cement tissue of the teeth with necrotic pulps and radiographic pathology. Thus, it can be assumed that after lesion formation, the permeability on the pulpal floor may also increase due to pathological changes.…”
Section: Introductionmentioning
confidence: 99%